Physical Performance of Cross-Laminated Panels Made from Nypa fruticans (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
The increasing demand for renewable and sustainable construction materials has led to the exploration of underutilised tropical biomasses for engineered wood applications. Nypa fruticans (nipah palm), abundant in Southeast Asian mangrove ecosystems, possesses fibrous, lignified petioles suitable for composite panel production. Despite that, the application in cross-laminated panel (CLP) manufacturing remains largely unexplored. This study addresses the knowledge gap by evaluating the physical performance of CLP fabricated from N. fruticans, focusing on density, moisture content, thickness swelling, and water absorption. The panels were fabricated at three target densities (400, 600, and 800 kg/m³) using long fibre strips and a bio-based epoxy resin at a 3:1 resin-to-hardener ratio. Hot-pressing was conducted at 7 MPa for 15 minutes at 100 °C. The fabricated panels were tested according to JIS A 5908:2003 standards. Results revealed that increased panel density significantly reduced moisture content, with values decreasing from 15.84% at 400 kg/m³ to 13.65% at 800 kg/m³. While only the lowest-density group exceeded the JIS moisture content limit, thickness swelling across all groups remained within the acceptable range, showing improved stability with increasing density. Water absorption demonstrated the most significant density-dependent variation, with the 800 kg/m³ panel absorbing 20% less moisture than the 400 kg/m³ counterpart. Statistical analysis via ANOVA confirmed the influence of density on all measured parameters (p < 0.001), and Duncan’s post-hoc test highlighted significant group differences. In conclusion, N. fruticans is a promising sustainable raw material for CLP production, with the 800 kg/m³ configuration exhibiting optimal performance. These findings supported the viability of the Nipah palm in engineered panel applications and contributed to the diversification of tropical biomass resources in eco-friendly construction materials.